Pusat Informasi dan Konseling Masyarakat di SMP Muhammadiyah Al-Mujahidin dan SMP Negeri 2 Playen, Gunungkidul, Yogyakarta - Agus Supriyanto; Wahyu Nanda Eka Saputra; Musfirah Musfirah (Bagimu Negeri, 2017)
AbstractCirculation and drug abuse appear as a lack of understanding of the students about the impact of drugs. School counselors have a role in preventive efforts to prevent circulation and abuse in the school environment through counseling and counseling services in the Information and Counseling Center program in peer guidance and peer counseling. The purpose of the Information and Counseling Center program is as a precautionary measure of drug abuse and abuse, as well as insights into the implementation of peer guidance and peer counseling. Method of execution through counseling, training, and forum discussion group. The program targets are students and counselors at SMP Muhammadiyah Al-Mujahidin Playen and SMP Negeri 2 Playen, Gunungkidul, Yogyakarta. Evaluate the implementation through group discussion forums with policymakers. The results of the implementation of the Information and Counseling Center program is the emergence of an understanding of students, counselors, and the school about emergency drugs in Playen, Gunungkidul as a tourist environment as well as development of peer guidance and peer counseling skills on students and counselors. The hope of the program is the development of government policies for the application of the Center for Information and Counseling Services at schools. Keywords: Information and Counseling Center, Drug Prevention